As histórias da pesquisa em educação ambiental no Brasil: memórias de um campo complexo e plural - Silva, Luiz Gustavo Veríssimo e (Universidade Federal de São Carlos, 2026)
In recent decades, we have been living through a global socio-environmental crisis that has raised questions about the ways we relate to the world. This movement has fostered the creation of major national and international conferences and debates related to environmental education, as well as supporting the development of laws, treaties, public policies, and a great deal of research. All of this is part of a history that is almost always the basis for the writing of academic works that address themes related to environmental education. This history is extremely important for the constitution of this field of research; however, when we look at it, we ask ourselves: are there other histories of research in environmental education? To answer this question, we conducted a qualitative study in which we interviewed researchers in environmental education, with the aim of developing understandings about the meanings they produce regarding this field of research based on their memories. The data were analyzed based on dialogic discourse analysis, grounded in the thinking of Mikhail Bakhtin and the Bakhtin Circle. From the articulation between a narrative considered “official” in the history of environmental education, the memories of the interviewed subjects, and our analytical perspective, we constructed three histories: a first one, organized around historical milestones, events, legislation, and data on academic production; a second, composed of the narratives of the researchers; and a third, which emerges from the dialogic analysis of these memories. The results show that research in environmental education in Brazil is constituted as a plural, heterogeneous, and multifaceted field, marked by disputes over meaning, by different political-pedagogical projects, and by diverse educational trajectories. The analyzed narratives show that there is not a single history of environmental education, but multiple histories in which subjects occupy varied positions in the discursive arena that is the field of research in environmental education. The study also highlights the centrality of collectives, networks, and partnership relations in the constitution of researchers’ trajectories, as well as the importance of the subjective dimension, life experiences, and historical contexts in the production of meanings about environmental education and about research itself. By problematizing the official history as an ideological construction that tends to erase conflicts, displacements, and subjects, the dissertation proposes to understand the history of research in environmental education as a permanent becoming. Finally, we conclude that telling histories of environmental education implies recognizing its unfinished, dialogical, and situated character, and that incorporating the memories of subjects makes it possible to broaden and complexify the understanding of the constitution of this field of research in Brazil.
Histories of Environmental Education Research in Brazil: Memories of a Complex and Plural Field
Keywords: Narrativas; Trajetórias formativas; Análise dialógica do discurso; Narratives; Formative trajectories; Dialogical discourse analysis; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; 13. Ação contra a Mudança Global do Clima